Essential oils in Vietnamese coriander leaves (Persicaria odorata), torch ginger flower (Etlingera elatior) and galangal (Alpinia galangal) / Muhammad Izwan Anuar - Anuar, Muhammad Izwan (Faculty of Applied Sciences, 2009)
Essential oil plants and culinary herbs include a broad range of plant species that are used for their aromatic value as flavoring in food, beverage, fragrance in pharmaceutical and industrial products. Vietnamese coriander leaves (Persicaria odorata) has triacethyl-alpha-terpeniol (eucalyptol or linalool) (73.52%) is the main component of the essential oil in this herb. In torch ginger flower (Etlingera elatior), its main component is 2-methyl-2-propenal diethylhydrazone (43.64%). While for the galangal (Alpinia galanga), the chemical constituents of this oil is cyclolongifolene oxide (31.72%). For this study, the essential oil of Vietnamese coriander leaves, torch ginger flower and galangal leaves were extracted by using hydrodistillation method and the components of essential oil in the herbs are determined by using gas chromatography-mass spectrometry.